GE_GERICHTE C/8449/2015 vom 25. September 2015 - GE Cour de justice (2015)
POURSUITE PAR VOIE DE FAILLITE; RADIATION(EFFACEMENT); CAPACITÉ D'ÊTRE PARTIE | LP.85a; LOJ.86; CPC.56; CPC.59; CPC.132; CPC.66; CC.52.1; CO.779.1